A Dual Inhibitor of Cdc7/Cdk9 Potently Suppresses T Cell Activation - Chen, Elijah W.; Tay, Neil Q.; Brzostek, Joanna; Gascoigne, Nicholas R. J.; Rybakin, Vasily (Frontiers in Immunology, 2019)
T cell activation is mediated by signaling pathways originating from the T cell receptor (TCR). Propagation of signals downstream of the TCR involves a cascade of numerous kinases, some of which have yet to be identified. Through a screening strategy that we have previously introduced, PHA-767491, an inhibitor of the kinases Cdc7 and Cdk9, was identified to impede TCR signaling. PHA-767491 suppressed several T cell activation phenomena, including the expression of activation markers, proliferation, and effector functions. We also observed a defect in TCR signaling pathways upon PHA-767491 treatment. Inhibition of Cdc7/Cdk9 impairs T cell responses, which could potentially be detrimental for the immune response to tumors, and also compromises the ability to resist infections. The Cdc7/Cdk9 inhibitor is a strong candidate as a cancer therapeutic, but its effect on the immune system poses a problem for clinical applications.